Expression of immunophenotypic markers in blood mononuclear cells of patients with advanced head and neck squamous cells carcinoma - Adriana Torres da Silva; Érica Leandro Marciano Vieira; Ana Cristina Simões e Silva; Andy Petroianu (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To evaluate peripheral blood mononuclear cells (PBMCs) from patients with advanced head and neck squamous cell carcinoma (HNSCC) in comparison with healthy volunteers, as they can be potential biomarkers. Methods: Immunophenotyping was performed using flow cytometry of blood mononuclear cells from two groups of adult men: group 1 (n = 14), diagnosed with HNSCC (mouth, larynx, and hypopharynx); and group 2 (n = 14), volunteers, healthy, and without the use of drugs. The cell groups studied were T lymphocytes (CD3, CD4, CD8, CD56 and CD69), B lymphocytes (CD19, CD69), neutrophils (CD11a, CD16, CD66b, HLA-DR), and monocytes (CD14, CD86). Results: In group 1, there were an increase in CD3+CD4+ T lymphocytes (p < 0.001) and NK 56+ cells (p = 0.009) and a decrease in CD3+CD8+ T lymphocytes (p = 0.02) in comparison with group 2. In patients with HNSCC, an increase was found in the expression of the CD69 marker in CD3+CD4+ T lymphocytes (p = 0.03) and CD19+ B lymphocytes (p = 0.01) when compared to healthy volunteers. Conclusion: HNSCC triggers a systemic inflammatory response with a decrease in CD8 T cells and an increase in CD4 T and CD56 natural killer cells. CD69 early activation marker was expressed by T and B cells.